Serum Concentrations and Subcutaneous Adipose Tissue mRNA Expression of Omentin in Morbid Obesity and Type 2 Diabetes Mellitus: the Effect of Very-Low-Calorie Diet, Physical Activity and Laparoscopic Sleeve Gastrectomy - URBANOVÁ, M.; DOSTÁLOVÁ, I.; TRACHTA, P.; DRÁPALOVÁ, J.; KAVÁLKOVÁ, P.; HALUZÍKOVÁ, D.; MATOULEK, M.; LACINOVÁ, Z.; MRÁZ, M.; KASALICKÝ, M.; HALUZÍK, M. (Physiological research, 2014)
Omentin is a novel adipokine with insulin-sensitizing effects expressed predominantly in visceral fat. We investigated serum omentin levels and its mRNA expression in subcutaneous adipose tissue (SCAT) of 11 women with type 2 diabetes mellitus (T2DM), 37 obese non-diabetic women (OB) and 26 healthy lean women (C) before and after various weight loss interventions: 2-week very-low-calorie diet (VLCD), 3-month regular exercise and laparoscopic sleeve gastrectomy (LSG). At baseline, both T2DM and OB groups had decreased serum omentin concentrations compared with C group while omentin mRNA expression in SCAT did not significantly differ among the groups. Neither VLCD nor exercise significantly affected serum omentin concentrations and its mRNA expression in SCAT of OB or T2DM group. LSG significantly increased serum omentin levels in OB group. In contrast, omentin mRNA expression in SCAT was significantly reduced after LSG. Baseline fasting serum omentin levels in a combined group of the studied subjects (C, OB, T2DM) negatively correlated with BMI, CRP, insulin, LDL-cholesterol, triglycerides and leptin and were positively related to HDL-cholesterol. Reduced circulating omentin levels could play a role in the etiopathogenesis of obesity and T2DM. The increase in circulating omentin levels and the decrease in omentin mRNA expression in SCAT of obese women after LSG might contribute to surgery-induced metabolic improvements and sustained reduction of body weight.